Ladder-type BN-embedded heteroacenes with blue emission - Wang, Xinyang; Zhang, Fan; Liu, Jun; Tang, Ruizhi; Fu, Yubin; Wu, Dongqing; Xu, Qing; Zhuang, Xiaodong; He, Gufeng; Feng, Xinliang (Organic Letters, 2013)
Using a concise synthetic strategy, a series of novel ladder-type BN-embedded heteroacenes were successfully synthesized. Their molecular skeletons render the versatile modification which is desirable for achieving unique physical properties. Organic light-emitting diode devices based on BN-embedded heteroacenes were subsequently fabricated, demonstrating their promising application as blue emitters. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20